Net primary productivity of forest trees: A review of current issue - Abdul Hamid, Hazandy; Mencuccini, Maurizio; Ab Shukor, Nor Aini (Universiti Putra Malaysia Press, 2009)
Forest growth is important both economically and ecologically and it follows a predictable general trend with age. Generally, the growth of all forests accelerates as canopies develop in young forests and declines substantially soon after the maximum leaf area is attained. The causes of this decline trend are multiple. Initially, age- and size-related declines were attributed to photosynthesis-respiration imbalance. Subsequently, several competing hypotheses have been proposed over the years, although nutrient and hydraulic limitation hypotheses appear to be the most likely to have caused it. In this paper, the authors attempt to review these hypotheses and concentrate on one related aspect, as this can set the scene for further examining the issues of age-related versus size-related processes.